THIOGLYCOL IN EXTENDER IMPROVES THE POST-THAW QUALITY OF BUFFALO (BUBALUS BUBALIS) BULL SPERMATOZOA - M. S. Ansari; B. A. Rakha; S. M. H. Andrabi; N. Ullah; R. Iqbal; W. V. Holt; S. Akhter (Journal of Animal and Plant Sciences, 2014)
This study was designed to evaluate the effect of thioglycol in extender on post-thaw quality of Nili-Ravi buffalo (Bubalus bubalis) bull spermatozoa. Semen from three buffalo bulls was collected at weekly intervals (three replicates; two ejaculates per bull per replicate) and qualifying ejaculates (n=18) were cryopreserved in extenders containing thioglycol at 0.0 or 0.5 or 1.0mM. Sperm motility (%; visually), plasma membrane integrity, (%;supravital hypo-osmotic swelling test), viability (%;dual staining technique using Trypan blue and Giemsa stains) and DNA integrity (%;acridine orange test) was assessed at 0, 2 and 4 hour post-thaw. Sperm motility, plasma membrane integrity and viability of buffalo bull spermatozoa were improved in a dose dependent manner with the supplementation of thioglycol at 0.5 mM and 1.0mM compared control. Sperm DNA integrity was similar (P>0.05) in extenders containing 0.5 mM and 1 mM thioglycol that remained higher (P < 0.05) than the values of DNA integrity in control. It is concluded that 1.0mM thioglycol in extender improved the motility, plasma membrane integrity, viability and DNA integrity of buffalo bull spermatozoa.
Keywords: Buffalo bull spermatozoa; thioglycol; cryopreservation